2017
DOI: 10.3892/etm.2017.4233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of icariin on fracture healing in an ovariectomized rat model of osteoporosis

Abstract: Abstract. Osteoporosis is frequently asymptomatic, presenting a significant clinical and economic burden, particularly following an osteoporosis-associated fracture. Icariin has been reported to inhibit osteoporosis in vitro, and the present study investigated whether icariin also promoted bone fracture healing in ovariectomized osteoporotic (OVX) rats in vivo. A total of 30 female rats were randomly divided into three groups (n=10 per group): i) Sham surgery; ii) OVX; and iii) OVX with icariin (OVX + ICA) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…It was report-ed that the bone loss caused by ovariectomy depends on the degree of skeletal area and the time since ovariectomy. Cao et al [4] examined the effect of icariin on fracture healing in an ovariectomised patient and reported that the use of icariin may help to improve fracture healing in postmenopausal osteoporosis and can be improved as an alternative therapy. The effect of oestrogen deficiency was reduced bone mass due to increased bone resorption and increased osteoclastic activity and also decreased new bone formation due to decreased osteoblastic life.…”
Section: Discussionmentioning
confidence: 99%
“…It was report-ed that the bone loss caused by ovariectomy depends on the degree of skeletal area and the time since ovariectomy. Cao et al [4] examined the effect of icariin on fracture healing in an ovariectomised patient and reported that the use of icariin may help to improve fracture healing in postmenopausal osteoporosis and can be improved as an alternative therapy. The effect of oestrogen deficiency was reduced bone mass due to increased bone resorption and increased osteoclastic activity and also decreased new bone formation due to decreased osteoblastic life.…”
Section: Discussionmentioning
confidence: 99%
“…This should be related to the effect of icariin on osteoblasts and osteoclasts. This situation might be clarified by icariin's simulative effects on osteoblasts, inhibition of osteoclast differentiation [5,6] and suppression of osteoclastogenesis. [7] Recent meta-analysis about in vivo studies of icariin indicates that icariin has a high osteo-inductive potential as a biomaterial for use in bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In addition, the flavonoids of Herba Epimedii have been shown to concurrently improve osteogenic differentiation and inhibit the osteoclastic differentiation of human bone marrow-derived cells. [4] It is suggested that Epimedium-derived flavonoids including icariin have an anabolic effect on osteoporotic bone by concomitantly promoting the osteogenic differentiation of bone marrow stromal cells [5,6] while suppressing adipogenic differentiation. [7] Fracture healing and bone repair which may result in unfavorable extension involve a combination of a series of complicated processes.…”
mentioning
confidence: 99%
“…Mice in the other two groups, the sham group, and the ACLT group were treated with the same amount of normal saline, once into the joint. The icariin treatment doses were chosen according to the findings from previous pharmacological studies [ 17 , 18 ]. In vitro , icariin was administered into the chondrogenic medium at concentrations of 10 −7 M, 10 −6 M, and 10 −5 M.…”
Section: Methodsmentioning
confidence: 99%